(untitled) (Eurasian Journal of Humanities and Social Sciences, 2026)
This article examines the ethnocultural foundations of developing a healthy lifestyle culture in modern society. It highlights that a healthy lifestyle is not only a medical or socio-economic issue, but also a socio-philosophical phenomenon rooted in national traditions, cultural values, and historical experience. The study analyzes the role of ethnocultural factors such as family upbringing, traditional knowledge, dietary practices, and folk pedagogy in shaping health-related behaviors. Special attention is given to the relationship between cultural values and sustainable lifestyle practices, including harmony with nature, moral development, and social responsibility. The findings suggest that integrating ethnocultural heritage with modern scientific approaches enhances the effectiveness of promoting a healthy lifestyle culture.